Characterization of the ignition and combustion processes of spray injected by a hole-type nozzle for a direct-injection spark ignition engine. (May 2014) - Chen, Run; Nishida, Keiya; Kataoka, Hajime
The spray-guided direct-injection spark ignition engine needs a stable ignition and combustion system for favourable operation. In this study, the effects of the ignition position (e.g. upstream, middle or downstream of the spray) and the timing (e.g. before, at or after the end of injection) respectively on the flame development and combustion processes of gasoline spray injected by a hole-type nozzle were investigated in a quiescent constant-volume vessel. OH* chemiluminescence was used to characterize the temporal and spatial distributions of the combusting activity and flame evolution. The soot formation process was clarified by using the high-speed imaging of two-colour pyrometry. At all the ignition positions, a moderate jet-to-jet variation in the maximum integrated OH* intensity was present as the fuel was ignited in the middle region of the spray. The over-lean mixture at the spark gap led to early flame decay and enhanced the variation in the combustion intensity. When the flame started to propagate, the decreased equivalence ratio distribution downstream of the ignition position tended to result in incomplete combustion with a pronounced long narrow flame shape and lower OH* emissions. The flame was impeded owing to the lean unburned mixture and the high flow velocity greater than the flame speed above the ignition position, causing it to propagate towards upstream of the spray. An over-rich mixture produced more soot during combustion, in accordance with the KL factor distribution. A potentially favourable condition for development of the flame and the combustion process was found when the fuel was ignited in the middle region of the spray, and the time when the injection was ended.